Analisis Pengaruh Kepemimpinan Gen Z dan Lingkungan Kerja Terhadap Kinerja Pegawai di PT XYZ - Muh Adzam (Yayasan Cendekia Gagayunan Indonesia, 2025)
The ever-evolving work environment demands companies to adapt to new generations entering the labor market, including Generation Z (Gen Z) born between 1997–2012 and now beginning to dominate the workplace with collaborative, flexible, and technology-savvy characteristics. This study aims to analyze the influence of Gen Z leadership style and work environment on employee performance at PT XYZ, which is transitioning to digital. The research method uses a quantitative approach with 60 respondents through a Likert scale questionnaire, analyzed using multiple linear regression. The results show that Gen Z leadership style and work environment simultaneously have a significant effect on employee performance (F = 111.79; p < 0.01), with the partial influence of Gen Z leadership style being more dominant (t = 6.30; p < 0.01) than the work environment (t = 2.63; p < 0.05). The coefficient of determination (R² = 0.8922) indicates that 89.22% of the performance variation can be explained by these two variables, while the remainder is influenced by other factors outside the model. These findings confirm that Gen Z's collaborative, flexible, and technology-based leadership style and comfortable work environment significantly contribute to improved performance, with practical implications for PT XYZ to strengthen leadership strategies and create adaptive work policies in the era of digital transformation.